Ultra wideband antenna for on-body communication systems - Jaber, Manhal Jaafar (2014)
Ultra-Wideband (UWB) is the technology declared in IEEE 802.15.6 which is the Ultra-Wideband (UWB) standard for Wireless Body Area Network (WBAN) published in 2012. The need for WBANs come originally from medical purposes, the key component of WBANs is the design of the UWB antenna which faces many challenges, including power consumption, size, frequency, the required band width, and the determination of losses caused by the human body tissues. There are some types of UWB antennas which are used for WBANs exist, The project aims for comparison between the characteristics of these antennas, and then follow it by a design of an antenna, this antenna faces less effects from the human body tissues, and gives a better performance in the simulations, avoiding all the complexities that been mentioned. The Design of the antenna uses CST Microwave Studio, to investigate the characteristics of the proposed antenna and optimize it, also the the fabrication has been done on FR4 PCB substrate, and all the required testing and comparison has been done. The effect of wearable antenna on the human body has been also investigated using homogeneous human body (muscle) model with distance of 5mm. The research works in this paper has demonstrated that UWB antenna using microstrip fed and coaxial probe as radiating element can be used for WBANs without effecting the human body, and achieves a very high bandwidth that can be used to transmit any kind of data. The small size of the antenna also provides no problem for the human comfort